Meta‐analytic evidence for altered mesolimbic responses to reward in schizophrenia. Issue 7 (24th March 2018) - Chase, Henry W.; Loriemi, Polina; Wensing, Tobias; Eickhoff, Simon B.; Nickl‐Jockschat, Thomas
Abstract: Dysfunction of reward‐related neural circuitry in schizophrenia (SCZ) has been widely reported, and may provide insight into the motivational and cognitive disturbances that characterize the disorder. Although previous meta‐analyses of reward learning paradigms in SCZ have been performed, a meta‐analysis of whole‐brain coordinate maps in SCZ alone has not been conducted. In this study, we performed an activation likelihood estimate (ALE) meta‐analysis, and performed a follow‐up analysis of functional connectivity and functional decoding of identified regions. We report several salient findings that extend prior work in this area. First, an alteration in reward‐related activation was observed in the right ventral striatum, but this was not solely driven by hypoactivation in the SCZ group compared to healthy controls. Second, the region was characterized by functional connectivity primarily with the lateral prefrontal cortex and pre‐supplementary motor area (preSMA), as well as subcortical regions such as the thalamus which show structural deficits in SCZ. Finally, although the meta‐analysis showed no regions outside the ventral striatum to be significantly altered, regions with higher functional connectivity with the ventral striatum showed a greater number of subthreshold foci. Together, these findings confirm the alteration of ventral striatal function in SCZ, but suggest that a network‐based approach may assist future analysis of the functional underpinnings of the disorder.